Reading Fluency Current Insights from Neurocognitive Research and Intervention Studies - Khateb, Asaid; Bar-Kochva, Irit (Literacy Studies, Perspectives from Cognitive Neurosciences, Linguistics, Psychology and Education, 2016)
The book is dedicated to the blessed memory of Prof. Zvia Breznitz, whose groundbreaking research has made a tremendous impact on the understanding of fluency in reading. The book presents a multidimensional perspective of recent research and reviews on fluency in reading. The first part presents recent brain-imaging findings from studies into the neurobiological basis of reading, as well as cognitive and language studies exploring the underlying factors of fluency in reading and its development. The second part comprises reviews of intervention studies that address reading ability, and in particular, fluency in reading. The book provides a unique multilingual perspective on reading research by including studies of readers of different orthographies and speakers of different languages. Both scientists exploring the different aspects of reading and language, and clinicians of reading intervention will find this book not only of great interest but extremely useful in its clear and in-depth presentation of current reading research.